Effectiveness of a peer-led adolescent mental health intervention on HIV virological suppression and mental health in Zimbabwe: protocol of a cluster-randomised trial. (2020) - Chinoda, Silindweyinkosi; Mutsinze, Abigail; Simms, Victoria; Beji-Chauke, Rhulani; Verhey, Ruth; Robinson, Joanna; Barker, Taryn; Mugurungi, Owen; Apollo, Tsitsi; Munetsi, Epiphany; Sithole, Dorcas; Weiss, Helen A.; et al.
Abstract: Background: Adolescents living with HIV (ALHIV) experience a high burden of mental health disorder which is a barrier to antiretroviral therapy adherence. In Zimbabwe, trained, mentored peer supporters living with HIV (Community Adolescent Treatment Supporters – CATS) have been found to improve adherence, viral suppression and psychosocial well-being among ALHIV. The Friendship Bench is the largest integrated mental health programme in Africa. We hypothesise that combining the CATS programme and Friendship Bench will improve mental health and virological suppression among ALHIV compared with the CATS programme alone. Methods: We will conduct a cluster-randomised controlled trial in 60 clinics randomised 1:1 in five provinces. ALHIV attending the control arm clinics will receive standard CATS support and clinic support following the Ministry of Health guidelines. Those attending the intervention arm clinics will receive Friendship Bench problem-solving therapy, delivered by trained CATS. Participants with the signs of psychological distress will be referred to the clinic for further assessment and management. The primary outcome is HIV virological failure (≥1000 copies/ml) or death at 48 weeks. Secondary outcomes include the proportion of adolescents with common mental disorder symptoms (defined as Shona Symptom Questionnaire (SSQ-14) score ≥8), proportion with depression symptoms (defined as Patient Health Questionnaire (PHQ-9) score ≥11), symptom severity (mean SSQ-14 and PHQ-9 scores) and EQ-5D score for health-related quality of life. Conclusions: This trial evaluates the effectiveness of peer-delivery of mental health care on mental health and HIV viral load among ALHIV. If effective this intervention has the potential to be scaled-up to improve these outcomes. Trial registration: PACTR201810756862405. 08 October 2018.